Zero energy resonances in atomic processes within a plasma - Clauser, Cesar Fernando (2015)
We investigate different atomic processes that might occur in the interior of plasmas. In particular we apply the Final-State Interaction theory in order to study the behavior of the corresponding cross sections when the relative energy of a pair of charged particles in the initial or final states vanishes. Through this analysis we uncover the presence of zero - energy resonances for particular configurations of density and temperature. For fusion plasmas, these effects might have an important impact on the working conditions and performance of the reactor.